Effects of methylprednisolone on the duration of rocuronium-induced neuromuscular block: A randomized double-blind trial. Issue 39 (September 2017) - Geng, Weilian; Nie, Yuyan; Huang, Shaoqiang
Abstract: Background: We aim to investigate whether intraoperative use of methylprednisolone could affect the duration of rocuronium-induced neuromuscular blockade. Methods: A double blind, randomized, placebo-controlled trial was conducted. A total of 136 patients underwent gynecologic laparoscopic surgery were randomly divided into 3 groups: pregroup, receiving intravenous injection of methylprednisolone (40 mg) 30 minutes before induction of anesthesia; postgroup, receiving intravenous injection of methylprednisolone (40 mg) immediately after induction of anesthesia and intubation; and control group, receiving intravenous injection of normal saline. Patients were intravenously administrated with rocuronium 0.6 mg/kg, and changes in adductor policies evoked twitch responses were measured by ulnar nerve stimulator. Results: We found that all patients achieved maximum blockade effects, and there was no difference in onset time among the 2 groups. For time required to achieve train-of-four ratio (TOFR) 90%, pregroup (64.50 ± 10.52 minutes) and postgroup (65.29 ± 11.64 minutes) were significantly shorter than that of the control group (71.04 ± 10.55 minutes, P  = .027), whereas clinical duration and total duration were significantly shorter in the 2 groups received methylprednisolone than the control group. However, there was no significant difference between the 2 treatment groups either in clinical duration and total duration of muscle relaxants, or time required to achieve TOFR 90%. No significant difference was found in recovery index among the 3 groups. Conclusion: Our findings suggest that a single intravenous injection of methylprednisolone, no matter preoperatively or intraoperatively, could shorten the duration of rocuronium-induced neuromuscular blockade.